Pockets of Peace: A mixed methods, exploratory study of neighborhoods resilient to juvenile violence. Issue 1 (15th July 2022) - Leech, Tamara G. J.; Adams, Elizabeth
Abstract: Social science research has focused on hot spots of adolescent violence in marginalized urban neighborhoods for nearly a century. In contrast, in this study, we explore under‐resourced urban areas that do not experience high rates of adolescent violence: "pockets of peace." We use a mixed‐method approach to identify the sociodemographic, geographic, and criminological commonalities and differences between pockets of peace and other areas of concentrated disadvantage dealing with high rates of adolescent violence in Indianapolis, IN. More than one out of every ten of Indianapolis' areas of concentrated disadvantage meet the criteria to be labeled "pockets of peace." Quantitative data indicate that these areas have fewer prosocial institutions and experience lower homeownership rates than comparison under‐resourced areas, and qualitative data point toward rental stability and residential longevity as potentially salient social factors within these contexts. As an alternative to using statistics to control for the context of structural disadvantage, studying pockets of peace and other "cold‐spots" of adolescent violence presents an opportunity to understand community‐level resilience within the real, lived context of structural disadvantage.